Kemampuan Mengelola Konflik Perkawinan pada Pasangan yang Mengalami Kehamilan Pranikah di Kecamatan Batang Kapas Kabupaten Pesisir Selatan - Rendri, Sentia Monica (Indonesian Research Journal on Education, 2022)
Problems that occurred from the start appeared such as the presence of a child and work problems. Then this study aims to find out how the style of married couples in resolving marital conflicts who experience premarital pregnancy in Batang Kapas District, Pesisir Selatan Regency. The research that the author is doing here is afield research (Field Research) using a qualitative approach. This research was conducted in Batang Kapas District, Pesisir Selatan Regency and the informants in this study were 3 married couples and 3 closest family members. In collecting the required data, the author uses observation and interview techniques. While in the discussion, descriptive method is used, namely a method that describes the situation that occurs in the fieldsystematically. The results of this study indicate that the ability to manage marital conflict in couples who experience premarital pregnancy seen from the style of marital conflict resolution in Batang Kapas District, Pesisir Selatan Regency belongs to the medium category in resolving marital conflicts. This can be seen from the results of the research that the author did, that when there is conflict in marriage, a married couple always resolves marital conflict problems by discussing problems with their partners, always compromises first with their partners to open their minds to each other when talking, always cooperates with partners to solve problems. can find solutions to resolve marital conflicts, and also married couples always try to be able to understand their partners in resolving marital conflicts. The form of conflict resolution style applied by married couples is the Collaboration style (collaboration) and the Compromising style (compromise).